The Determinants of Leadership Style in Business School - Amborowati, Agustin; Harsono, Mugi (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
Leadership plays a central role in determining the direction, culture, and performance of an organization. In the context of globalization, an effective leadership style is becoming increasingly important, as leaders need to be able to face the various challenges facing organizations at the global level. Leadership style refers to the leader's methods and behaviors when directing, motivating, and managing others (Fonseca Da Costa Guterresa et al., 2020). A leader's style is shaped by a variety of factors, including personality, values, skills, and experience, and can have a significant impact on the effectiveness of their leadership. The research design used was in the form of a survey. The primary data source obtained in this study was carried out by distributing questionnaires directly to students. Secondary data sources in this study are Human Resource Management Books and previous research journals related to the research topic, namely about Leadership Style. In this study, researchers will describe the Leadership Style possessed by students. Generation Z shows a strong preference for participatory, collaborative and technology-oriented leadership. Participatory leaders listen to and value team input, promote collaboration, and create an inclusive environment (Hassan et al., 2016). This research makes an important contribution to our understanding of Generation Z's preferences and leadership styles in the global economy. These results can assist organizations, leaders, and academics in developing more effective leadership strategies to guide and support future leaders.